Ijarah Digital dalam Ekonomi Gig: Menuju Kerangka Tata Kelola Syariah pada Platform Freelancer: Digital Ijarah in the Gig Economy: Toward an Islamic Governance Framework for Freelance Platform Labor - Fitri Kurniawati; Nisa Amalia (JEIZA : Jurnal Ekonomi Islam Az-Zain, 2026)
This study examines the practice of digital labor leasing on freelance platforms from the perspective of fiqh ijarah. It aims to evaluate contract validity, worker protection, and Sharia compliance while proposing a conceptual Islamic governance framework for digital labor relations in the gig economy. A qualitative method with an Islamic legal phenomenology design was employed, supported by participatory observation, document analysis, and conceptual–propositional analysis. The findings indicate that although digital ijarah generally fulfills the essential elements of a valid contract, significant concerns remain regarding wage transparency, social protection, dispute resolution, and algorithm-driven work allocation. The asymmetry of power between platforms and workers challenges the realization of justice and fairness as emphasized in maqasid al-shariah. The study proposes a hybrid contract model integrating ijarah al-a'mal and musyarakah, combining wage-based compensation with risk-sharing principles to enhance distributive justice and sustainability. Technically, this model mitigates power asymmetry by introducing transparent algorithmic wage parameters, profit-sharing mechanisms tied to worker contribution, and embedded social protection features that redistribute risk more proportionally between platform and workers. Theoretically, this research contributes to the development of contemporary fiqh muamalah by formulating a Sharia-based governance model adaptable to digital platforms. Practically, it offers policy and regulatory insights for designing equitable digital contracts and strengthening worker protection within the gig economy.